Re-Design Tryout Wangsit Mobile Apps using Learner Centered Design Method - Firyal Yamiza Akbar -; Ati Suci Dian Martha; Dawam Dwi Jatmiko (STMIK Budi Darma, 2023)
The many variants of subjects with varying difficulty levels cause some students to have difficulties understanding the material. Some students who find it challenging start attending tutoring provided by teachers or various tutoring centers and purchase practice question books to better grasp the material they haven't mastered. One of the books is the Wangsit learning book. Wangsit is one of the best-selling exercise books among high school 12th students in Indonesia. Wangsit provides a learning aid called the Wangsit tryout mobile application, which serves as an app for conducting practice tests and providing video learning materials. However, there are user interface issues related to the application, such as the placement of several buttons on the tryout page being less than optimal, which requires learners to become more accustomed to it and the score page of the tryout lacks clear information about the test results. Usability measurement was conducted using the System Usability Scale (SUS) with 8 respondents who were 12th-grade students and had Wangsit om Jero’s book. The obtained System Usability Scale score was 43.75. This study aims to redesign the interface display of the Tryout Wangsit mobile application to make the Wangsit tryout mobile application suited to the learners' needs by using the learner-centered design method, which focuses on learners' learning experiences. The objective was to improve the usability of the Tryout Wangsit mobile application and align it with learners' needs. The study resulted in a redesigned interface display for the Tryout Wangsit Mobile application using the learner-centered design method. As a result, the application achieved an improved System Usability Scale (SUS) score of 83.12.